If Crisis Comes - Johansson, Susann; Mähler, Linnéa (Bobcatsss, 2023)
Since a worldwide pandemic is a new phenomenon in the modern era, the outbreak of COVID-19 during the spring of 2020 resulted in Swedish libraries having to restructure their daily operations regarding the physical library and in-person services. The purpose of this paper is to present how the university libraries in Sweden responded to the imposed government directions. While reviewing several universities’ crisis plans, it became apparent that guidelines for pandemics were missing: this in turn led to different solutions for each university library. The paper analyses these solutions to see how well-prepared the university libraries in Sweden were, and how the libraries fulfilled their obligations to patrons and society while working under the directions from Folkhälsomyndigheten (the Swedish National Healthy Agency). Data regarding the libraries’ responses to the pandemic was collected from each library’s website; all data was collected on the same date, to make comparisons between the different libraries possible. The data was then analysed using quantitative content analysis, where the actions taken by the different libraries were sorted into a number of predetermined categories. These categories were determined using information from crisis plans, The Swedish Higher Education Act (1992:1434), and actions taken by libraries during previous pandemics. Among the study’s findings are drastically reduced opening hours and the conversion of a majority of in-person services to digital services. Earlier studies in the United States indicate that libraries need reliable e-learning systems and digital platforms in case of a worldwide pandemic, as well as guidelines for the acquisition of new software and digital services. The findings of this study indicate that such systems are already in place at a majority of Swedish university libraries, which made the transition to digital services smoother. This paper provides insights into the different actions taken by the university libraries in Sweden during the COVID-19 pandemic, and how these actions affected the daily operations for university libraries all over the country. The study can therefore be used as a basis for further studies regarding assessments of different approaches to crisis, and for determining what course of action to take in a future similar crisis.